Immunoglobulin G4-Related Retroperitoneal Fibrosis Treated with Hochuekkito, a Kampo Medicine, following Steroid Treatment - Fukuchi, Minoru (S. Karger AG, 2014)
We report a case of immunoglobulin G4 (IgG4)-related retroperitoneal fibrosis (RF) with complete remission and no relapses after therapy with steroids and Hochuekkito, a Kampo (i.e. traditional Japanese herbal) medicine. A 62-year-old Japanese man was admitted to our hospital for treatment of a retroperitoneal mass detected by computed tomography. The mass had a maximum diameter of 11.0 cm; it involved the left ureter and was associated with left hydronephrosis. After inserting a ureteral stent, we performed a biopsy by laparotomy. Histopathology revealed IgG4-related RF. The lesion disappeared after 7 months of steroid therapy. We subsequently used Hochuekkito as an alternative maintenance treatment because of steroid-related complications. The patient has not relapsed in the 3 years since starting the medication. To the best of our knowledge, this is the first case of IgG4-related RF treated with Hochuekkito as a maintenance treatment.